THE ROLE OF THE SCHOOL IN HEALTH EDUCATION - Cardoso, Gildon (Revista Gênero e Interdisciplinaridade, 2023)
What is the perception that teachers have about the school’s role in health education? This was the starting question for this research, which was carried out at the Primary School of Mapara, in the city of Nampula, whose data collection was carried out based on a questionnaire to be completed by three randomly selected teachers in three different class periods, having left their perceptions in writing as the study methodology. Professors were coded as Professor 1, Professor 2 and Professor 3. This work was carried out as a condition for the completion of the Curriculum Design module in Health Teaching, at the Faculty of Health Sciences at Lúrio University. The research aims to analyze the perception of teachers about the role of the school in education for health, as a way of understanding their contributions to the perception of this matter. From the analysis carried out, it was concluded that the school plays a very important role of transmitter and trainer in changing attitudes towards a healthy school community and that teachers play a very crucial role in being facilitators for healthy habits at school, which will later also reflect in the community through the training of students.